Establishing and Financing Islamic Channels and Websites from Zakat Funds. A Comparative Jurisprudence Study - Al Sheehah, Ahmad Abdulrahman (Journal of Ecohumanism, 2024)
The study addresses the establishment and funding of Islamic channels and websites using zakat funds, highlighting the differing opinions among jurists regarding interpreting the seventh category of zakat expenditures, known as (the path of Allah). It explores whether this category is limited to conquest and ribat or if it also encompasses the promotion of Allah's message through modern communication and media methods. This subject was explored in three distinct sections: The discussion started with an explanation of Zakat, its significance in Islam, and its legal purposes. It then outlined the categories of Zakat in general, clarified the meaning of the category about the path of Allah, discussed the opinions of jurists regarding it, and elaborated on the legitimacy of financing Islamic channels and websites from the funds allocated to this category. The research concluded with a summary that encompasses the key findings and recommendations.